Strategi Pengembangan E-Commerce Dalam Rangka Memajukan UMKM Untuk Pembangunan Berkelanjutan - Abdul Halim Anshor (Prosiding Sains dan Teknologi, 2022)
Currently, the development of information technology is very fast, this is able to create various kinds of changes in life into the digital world, one of which is the digital economy. This condition has created digital technology in the economic field, namely E-commerce which is an activity of distributing, selling, purchasing, marketing products (goods and services), by utilizing the internet network. With the globalization of information technology has brought the economy to sharp competition among business actors, both local and international. Economic development in Indonesia cannot be separated from the role of micro, small and medium enterprises (MSMEs). The number of MSMEs in Indonesia is always increasing from year to year. The pandemic condition has made the Indonesian and world economies experience a very significant decline, this demands the need for innovation in existing economic problems. one of them is by developing an E-commerce strategy in the field of micro, small and medium enterprises (MSMEs), where it is hoped that this step can help in economic recovery, especially in Indonesia so that sustainable development can be realized in this country. The research carried out aims to determine the E-commerce development strategy to promote MSMEs with qualitative and quantitative SWOT (Strength Weakness Opportunity Threat) analysis methods. From this research, it is known the current condition of E-Commerce development and how the strategy is to advance existing MSMEs, taking into account the strengths and weaknesses as well as existing opportunities and threats, the position of MSMEs by adopting E-Commerce has the opportunity to grow big and advance so that this can be achieved. contribute to the sustainable development of the country. Keywords: Digital, E-commerce, Pandemic, MSME, SWOT